2004
DOI: 10.1002/14651858.cd003545.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoperazine for schizophrenia

Abstract: Analysis 2.4. Comparison 2 TRIFLUOPERAZINE versus TYPICAL ANTIPSYCHOTICS, Outcome 4 Global state: 1e. No substantial improvement-subgroup analysis-mixed diagnoses vs schizophrenia only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 89 publications
0
36
0
5
Order By: Relevance
“…The agent associated with the least risk of daytime somnolence is aripiprazole, which was associated with a 12% incidence of this adverse effect. Quetiapine and ziprasidone were also relatively less likely than the other agents to cause daytime sleepiness, with a 16% rate of reported somnolence Fenton et al, 2000;Gilbody et al, 2000;Thornley et al, 2003;Marques et al, 2004;Srisurapanont et al, 2004;Duggan et al, 2005;El-Sayeh and Morganti, 2006;Jayaram et al, 2006;Joy et al, 2006). The relatively low somnolence rate associated with quetiapine and ziprasidone is notable considering that the studies reviewed in the previous section would suggest that both agents have the capacity to significantly enhance sleep in terms of increasing total sleep time and decreasing awakenings ( Table 2).…”
Section: Daytime Sedationmentioning
confidence: 98%
See 1 more Smart Citation
“…The agent associated with the least risk of daytime somnolence is aripiprazole, which was associated with a 12% incidence of this adverse effect. Quetiapine and ziprasidone were also relatively less likely than the other agents to cause daytime sleepiness, with a 16% rate of reported somnolence Fenton et al, 2000;Gilbody et al, 2000;Thornley et al, 2003;Marques et al, 2004;Srisurapanont et al, 2004;Duggan et al, 2005;El-Sayeh and Morganti, 2006;Jayaram et al, 2006;Joy et al, 2006). The relatively low somnolence rate associated with quetiapine and ziprasidone is notable considering that the studies reviewed in the previous section would suggest that both agents have the capacity to significantly enhance sleep in terms of increasing total sleep time and decreasing awakenings ( Table 2).…”
Section: Daytime Sedationmentioning
confidence: 98%
“…The adverse effect data appearing in Table 3 were compiled from the Cochran reviews of the available controlled trials with each of these agents (Allison et al, 1999;Bagnall et al, 2000;Fenton et al, 2000;Gilbody et al, 2000;Thornley et al, 2003;Marques et al, 2004;Srisurapanont et al, 2004;Duggan et al, 2005;El-Sayeh and Morganti, 2006;Jayaram et al, 2006;Joy et al, 2006). Adverse event reporting is particularly poorly suited in determining the relative degree to which weight gain occurs with therapy.…”
Section: Sleep-wake Function-related Adverse Effectsmentioning
confidence: 99%
“…Nevertheless, the reviewed literature showed that the incidence and average dose of chlorpromazine prescribed to people with schizophrenia has been decreasing 22. Other commonly used FGAs such as trifluoperazine, thioridazine, sulpiride, pimozide, perphenazine, and fluphenazine were tested and confirmed to have similar and satisfactory efficacy in symptom reduction – mainly for positive symptoms (eg, delusions and hallucinations) 2328. However, there was limited evidence to support their efficacy at lower doses or in short-term treatment 2831.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Its potency, however, combined with little inherent antimuscarinic activity, means that EPS liability is high. Despite little anticholinergic action in vitro, its use may still be associated with dry mouth, blurred vision and so on (Marques 2004), symptoms usually attributed to muscarinic blockade. This may, however, reflect an unduly narrow interpretation of how such symptomatology arises or the activity of metabolites rather than the parent drug.…”
Section: Perphenazine (Table 4)mentioning
confidence: 99%
“…Although trifluoperazine can be sedative (Marques 2004), especially at high dose, clinical experience suggests that, compatible with its binding profile, it is one of the least sedative antipsychotics. Originally, much was made of its 'alerting' properties, particularly in longterm institutionalised patients (Gwynne 1962), something also inferred from improvements in psychomotor abilities and speed of performance (to some extent dose-related) reported in healthy volunteers (DiMascio 1963a).…”
Section: Perphenazine (Table 4)mentioning
confidence: 99%